Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/socsci7030044
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Women’s Attitudes and Goals in Choosing Disciplines with Above and Below Average Female Representation

Abstract: Abstract:Women's participation in engineering remains well below that of men at all degree levels. However, despite the low enrollment of women in engineering as a whole, some engineering disciplines report above average female enrollment. We used multiple linear regression to examine the attitudes, beliefs, career outcome expectations, and career choice of first-year female engineering students enrolled in below average, average, and above average female representation disciplines in engineering. Our work beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…Many of the general results we find are consistent with other studies of empathy and gender. They are also consistent in large part with the study by Verdín cited in the Introduction [2]. This study finds that women gravitate to various engineering disciplines based on their individual match with several male associated qualities found in that discipline.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Many of the general results we find are consistent with other studies of empathy and gender. They are also consistent in large part with the study by Verdín cited in the Introduction [2]. This study finds that women gravitate to various engineering disciplines based on their individual match with several male associated qualities found in that discipline.…”
Section: Discussionsupporting
confidence: 88%
“…Our research specifically addresses how empathy affects women and is aimed at understanding the differences we observe in the representation of women in various engineering disciplines. In this respect, our research is in line with the recent work by Verdín in which the attitudes and goals of women were examined and found to affect their choice of major [2]. Although the methods used differ substantially, the conclusions are very similar -traits associated to a greater degree with women (which would include empathy) are correlated with choices of major.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Personality is relatively stable, unlike other frameworks used in this study, and it has been shown to distinguish engineering students from other students (Scott and Sedlacek 1975). Among engineering students, personality distinguishes those students who choose particular engineering disciplines (Verdín, Godwin, Kirn, Benson, & Potvin 2018) or degree pathways (Moses et al 2011).…”
Section: Big Five Personalitymentioning
confidence: 82%
“…Belongingness is an essential part of a student's educational experience, at both the classroom and university levels (T. M. Freeman, Anderman, and Jensen 2007;Wilson et al 2015). Prior work has also found that beliefs about seeing oneself as the type of person who can be an engineer had a positive effect on students' sense of belonging in the engineering field and classroom (Verdín et al 2018). Students most often describe belongingness as a feeling of comfort, specific skills or attitudes they possessed that fit with their degree programme, or enjoyment of their subject (Rohde et al 2018).…”
Section: Confidencementioning
confidence: 99%